PENGARUH FAKTOR INTERNAL DAN EKSTERNAL BANK TERHADAP NET INTEREST MARGIN DI INDONESIA - Indah Lestari Dewi, Gusti Ayu Putu; Triaryati, Nyoman (E-Jurnal Manajemen; Vol 6 No 6 (2017), 2017)
This  study aims to examine the influence of internal bank’s factors (Equity to Asset Ratio, Loan to Deposit Ratio, Non-PerformingLoan, Bank size, BOPO) and external bank’s factors (GDP growth and inflation) to Net Interest Margin at commercial banks on Indonesia Stock Exchange period 2013-2015. Multiple Linear RegressionAnalysis was used as an analytical technique. The studysample consisted of 41 commercial banks which were taken by census method where the overall population become sample. Financial statements of the commercial banks were used as a source of the secondary data in this study. The result of the internal factor showed that EA, LDR, Bank Size and BOPO have positive effect on NIM but NPL doesn’t have significant effect on NIM while the external factors both of GDP growth and Inflation don’t have significant effect on NIM. The slow growth of economic in Indonesia and the NIM fluctuation during the study period are the background of this study result.
Keywords: internal factors, external factors, NIM.